2016
DOI: 10.1007/s10653-016-9840-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological risks of the abandoned F–Ba–Pb–Zn mining area of Osor (Spain)

Abstract: Aquesta és una còpia de la versió author's final draft d'un article publicat a la revista Environmental geochemistry and health.La publicació final està disponible a Springer a través de http://dx.doi.org/10.1007/s10653-016-9840-2 This is a copy of the author 's final draft version of an article published in the journal Environmental geochemistry and health. AbstractDue to its potential toxic properties, metal mobilization is of major concern in areas surrounding PbZn mines. In the present study, metal conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
(34 reference statements)
7
15
3
Order By: Relevance
“…After decades, a large number of ores deposit in the surface soil with the help of rainfalls, with a maximum thickness of 3.2 cm. The concentrations of Zn and Pb in soil samples are much more variable among the sampling sites, with similar to the results of the Osor mine district (Bori et al 2017), and 100 times higher than those found at the Zeïda district (Morocco) (El Azhari et al 2017). Compared with the areas mentioned above, the trace metal pollution in soils and water caused by small mines in the Yanshan Mountains really deserves certain attention and vigilance.…”
Section: Resultssupporting
confidence: 82%
“…After decades, a large number of ores deposit in the surface soil with the help of rainfalls, with a maximum thickness of 3.2 cm. The concentrations of Zn and Pb in soil samples are much more variable among the sampling sites, with similar to the results of the Osor mine district (Bori et al 2017), and 100 times higher than those found at the Zeïda district (Morocco) (El Azhari et al 2017). Compared with the areas mentioned above, the trace metal pollution in soils and water caused by small mines in the Yanshan Mountains really deserves certain attention and vigilance.…”
Section: Resultssupporting
confidence: 82%
“…Our results agree with previous studies (Natal-da-Luz et al, 2009;Bori et al, 2016Bori et al, , 2017 and could be related to the relatively resistance of collembolans to metal(loid) contamination Hopkin, 2001, 2005). The preference response of F.…”
Section: Effects Of Soil Moisture Content On Invertebrates' Avoidance...supporting
confidence: 93%
“…Both Zn and Cu were in concentrations above the EC50 values established for R. subcapitata and D. magna (Table 5). The results were in accordance with metal concentrations obtained in industrial soils and from mining areas contaminated by trace metals [29]. Trace elements such as Zn can increase its toxicity (additive effect) by the presence of other trace metals (i.e., Co), this can explain the toxicity in the elutriates when only Zn and Cu were detected [30,40].…”
Section: Figuresupporting
confidence: 87%